Writing Through the 4Cs in the Content Areas – Integrating Creativity, Critical Thinking, Collaboration and Communication - Randa Saliba Chidiac; Laurence Ajaka (European Scientific Journal, ESJ, 2018)
Writing is a complex process that involves a number of competences and a degree of imagination. It can be evolved by using the 4Cs in the content areas: integrating creativity, critical thinking, collaboration, and communication, all of which teachers have struggled to include as part of their curricula. These struggles are often caused by logistic and financial constraints. With the professional demand pressingly navigating towards technology, teachers can aid their students by applying solution amenable to immediate use, low cost and tolerates interdisciplinary implementation. The first step would be to abandon the conventional curricula that were taught before as most of the current students are at a whole new technological level. They can be replaced by more pertinent skills that cater to the artistic and professional outlooks of students. This will ultimately equip them to be able to meet the market standards and improve their vocational prospects.